SEKOLAH LUAR BIASA DENGAN PENDEKATAN BIOFILIK DI KOTA SINGKAWANG - Damayanti, Amelia Firda; Putro, Jawas Dwijo; Alhamdani, Muhammad Ridha (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Education is essential to every citizen's existence. It does not exclude those with impairments (differently abled). Article 5 of The Law of the Republic of Indonesia Number 20 of 2003 states,